Biscarbamate Cross-Linked Low-Molecular-Weight Polyethylenimine for Delivering Anti-chordin siRNA into Human Mesenchymal Stem Cells for Improving Bone Regeneration - Wang, Chuandong; Yuan, Weien; Xiao, Fei; Gan, Yaokai; Zhao, Xiaotian; Zhai, Zhanjing; Zhao, Xiaoying; Zhao, Chen; Cui, Penglei; Jin, Tuo; Chen, Xiaodong; Zhang, Xiaoling (Frontiers in Pharmacology, 2017)
Small-interfering RNA (siRNA) provides a rapid solution for drug design and provides new methods to develop customizable medicines. Polyethyleneimine 25kDa (PEI25kDa) is an effective transfection agent used in siRNA delivery. However, the lack of degradable linkage causes undesirable toxicity, hindering its clinical application. We designed a low-molecular-weight cross-linked polyethylenimine named PEI-Et (Mn:1220, Mw:2895) by using degradable ethylene biscarbamate linkage with lower cytotoxicity and higher knockdown efficiency than PEI25kDa in delivery Chordin siRNA to human bone mesenchymal stem cells (hBMSCs). Suppression of Chordin by using anti-Chordin siRNA delivered by PEI-Et improved bone regeneration in vitro and in vivo via the bone morphogenetic protein-2 (BMP-2) mediated smad1/5/8 signaling pathway. Results of this study suggest that Chordin siRNA can be potentially used to improve ontogenesis via the BMP-2-mediated Smad1/5/8 signaling pathway and biodegradable biscarbamate cross-linked low-molecular-weight polyethylenimine (PEI-Et) is a therapeutically feasible carrier material to deliver anti-Chordin siRNA to hBMSCs.